2018
DOI: 10.1136/neurintsurg-2017-013701
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of blood blister aneurysms of the internal carotid artery with flow diversion

Abstract: Our data support the use of a flow diversion technique as a safe and effective therapeutic modality for BBA of the supraclinoid ICA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 21 publications
(3 reference statements)
1
56
1
Order By: Relevance
“…Specifically, the appropriate duration of dual (then single) antiplatelet therapy required to maintain the patency of the device and covered side branches remains uncertain; because of the need for dual antiplatelet medications, the use of PED in patients with acute subarachnoid haemorrhage remains controversial; and the safety and efficacy of PED use to treat bifurcation aneurysms remains unknown. Indeed, two recently published JNIS papers reporting the results on the use of PED in ruptured blister-like aneurysm3 and bifurcation aneurysms4 showed encouraging results, but data remain insufficient to consider using PED or other flow diverters in these challenging clinical situations.…”
mentioning
confidence: 99%
“…Specifically, the appropriate duration of dual (then single) antiplatelet therapy required to maintain the patency of the device and covered side branches remains uncertain; because of the need for dual antiplatelet medications, the use of PED in patients with acute subarachnoid haemorrhage remains controversial; and the safety and efficacy of PED use to treat bifurcation aneurysms remains unknown. Indeed, two recently published JNIS papers reporting the results on the use of PED in ruptured blister-like aneurysm3 and bifurcation aneurysms4 showed encouraging results, but data remain insufficient to consider using PED or other flow diverters in these challenging clinical situations.…”
mentioning
confidence: 99%
“…53,72 There were no major strokes or neurologic deaths at the 30-day or 1-year postprocedure follow-up, indicating the safety of the Pipeline Shield FD for use in intracranial aneurysm treatment. 11 Patients also had good clinical outcome, with mRS scores between 0 and 2 at the 3 month follow-up. Ninety percent of patients had immediate total or near occlusion of the blister aneurysm (1 patient's aneurysm remained patent; this patient died 10 days after initial rupture) and retained good function at 90 days postprocedure (8 patients had a modified Rankin Scale [mRS] score of 0, 1 patient had an mRS score of 1).…”
Section: Mechanism: Endothelializationmentioning
confidence: 83%
“…73 Mokin et al also showed safety of the PED FD in blood blister aneurysms of the ICA, with complete obliteration on angiographic follow-up in 87.5%, decreased filling in 9.4%, and persistent filling in only 3.1% of treated aneurysms. 11 Patients also had good clinical outcome, with mRS scores between 0 and 2 at the 3 month follow-up. These indicate the safety of FDs for both unruptured and ruptured aneurysm treatment.…”
Section: Mechanism: Endothelializationmentioning
confidence: 83%
See 2 more Smart Citations